Cyclophosphamide-induced hepatotoxicity in wistar rats: The modulatory role of gallic acid as a hepatoprotective and chemopreventive phytochemical - Ademola Adetokunbo Oyagbemi; Olutayo Temidayo Omobowale; Ebunoluwa Rachael Asenuga; Akinrinde Stephen Akinleye; Rachael Omolola Ogunsanwo; Adebowale Bernard Saba; Ademola Adetokunbo Oyagbemi; Olutayo Temidayo Omobowale; Ebunoluwa Rachael Asenuga; Akinrinde Stephen Akinleye; Rachael Omolola Ogunsanwo; Adebowale Bernard Saba (International Journal of Preventive Medicine, 2016)
Background: Gallic acid (GA) is an endogenous plant phenol known to have antioxidant, free radical scavenging ability, anti-inflammatory, anti-cancer, and anti-fungal properties. The aim of this study was to assess the protective effect of GA on cyclophosphamide (CPA)-induced hepatotoxicity in male Wistar rats. Methods: Sixty rats were grouped into six groups of 10 rats per group. Group 1 received distilled water. Group 2 received CPA at 200 mg/kg single dose intraperitoneally on day 1. Groups 3 and 4 received a single dose of CPA (200 mg/kg) intraperitoneally on day 1 and then were treated with GA at 60 and 120 mg/kg body weight for 14 days, respectively. Rats in Groups 5 and 6 only received GA at 60 and 120 mg/kg body weight for 14 days, respectively. GA was administered orally. Results: CPA induced hepatic damage as indicated by significant elevation (P < 0.05) in aspartate aminotransferase, organ weight, and evidence by the histological study. CPA also induced hepatic oxidative stress as indicated by significant elevation (P < 0.05) in malondialdehyde content, hydrogen peroxide (H 2 O 2 ) generation, nitrite level, and the level of glutathione (GSH) peroxidase crashed in the CPA-treated group. GA enhanced the antioxidant defense system as indicated by significant elevation (P < 0.05) in GSH level, catalase activity, and GSH-S-transferase activity. Conclusions: Taken together, the result of this present study shows that GA has a protective effect on CPA-induced hepatotoxicity.